PENGARUH MEDIA KARTU HURUF TERHADAP HASIL BELAJAR SISWA PADA SUBTEMA I HIDUP RUKUN DI RUMAH KELAS II UPTD SD NEGERI 122398 PEMATANG SIANTAR - Luisa Yanti Aprina Hia; Theresia Monika Siahaan; Winarto Silaban (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
This exploration means to decide the impact of letter card media on sub-subject I Residing as one at home to further develop the learning results of Class II UPTD understudies at SD Negeri 122398 Pematang Siantar. The examination configuration utilized is a quantitative methodology with a trial strategy as a one gathering pretest posttest plan without a correlation bunch. The populace in this review were all class II understudies at UPTD SD Negeri 122398 Pematang Siantar and the example utilized was 23 understudies at UPTD SD Negeri 122398 Pematang Siantar. The consequences of speculation testing utilizing the t test strategy matched example t test with the assistance of the SPSS Variant 21 program, in light of the computation results that the critical worth is 0.000 < 0.05, so ho is dismissed and ha is acknowledged or by impacting tcount > ttable with df = (n-1) to be specific the worth of tcount = 9.997> ttable = 1.717.